Sri Lankan Elephant in 17th Century Historical Record of Robert Knox: A Review - Kakulandala, K.; Bogahawatta, C. (Centre for Asian Studies, University of Kelaniya, Sri Lanka, 2016)
Robert Knox was a British sailor who was held captive in Ceylon for nineteen and a half years. After escaping from captivity, he wrote the manuscript, 'An Historical Relation of the Island Ceylon' and later published it in London in 1681. It was a descriptive account with illustrations of his experiences on Ceylon. Knox recorded many aspects of the country and its society, including royal administration, agriculture, religion, culture, education and bio-diversity. One of the significant aspects of his account was the description of Sri Lankan elephants at that time. Although many travelers who visited Sri Lanka had previously recorded the presence of elephants, they commented on them as a famous and luxurious commodity. Knox's record was the first descriptive travel account of elephants, rather than an emphasis on their commercial value. His statement "…the creature that this country is famed for above any in India" defined the deep-rooted idea of Sri Lankan elephants among foreigners at the time and expressed why he was interested in writing such a long narration on them. Further, it emphasized the need to review Knox's work based on a historical perspective when we are studying any aspect of the Sri Lankan elephant. Therefore the main objective of this study is to review his account to identify the condition of elephants at the time. Accordingly, it can be stated that the details of the nature of Sri Lankan elephants, attitudes of people, activities, capturing and taming of elephants as well as damages to the people by them can be followed from Knox's account.
Keywords: Robert Knox; ancient Ceylon; Sri Lankan elephant; travel accounts; commodity